Cervical cancer screening predictors in Tanzania: a variance component models’ approach of national survey 2022 - Jovin R. Tibenderana; Sanun Ally Kessy; Jomo Gimonge; Innocent Peter; Fabiola Moshi (Medicine, 2026)
Despite the potential for prevention through early detection and treatment, cervical cancer remains the most prevalent cancer among women of reproductive age (WRA). There is a paucity of evidence on the predictors influencing cervical cancer screening nationwide. Thus, this study aimed to determine the predictors associated with cervical cancer screening among WRA in Tanzania using the 2022 Tanzania Demographic and Health Surveys. This study was an analytical cross-sectional study that utilized nationally representative secondary data sourced from the Tanzania Demographic and Health Surveys of 2022. A weighted sample of 15,254 WRA (15–49 years) was included in the study. A multilevel binary logistic regression analysis was used to examine predictors associated with the uptake of cervical cancer screening services. These results were presented using adjusted odds ratios (AORs) with 95% confidence intervals (CIs). Predictors that were found to be significantly associated with cervical cancer screening among WRA in Tanzania were age (AOR = 7.12, 95% CI: 5.42–9.37), education (AOR = 2.58, 95% CI: 1.91–3.48), occupation (AOR = 1.3, 95% CI: 1.10–1.54), having visited a health facility in the past 12 months (AOR = 1.30, 95% CI: 1.13–1.51), the use of contraceptives (AOR = 1.23, 95% CI: 1.06–1.42), human immunodeficiency virus status (AOR = 5.56, 95% CI: 4.33–7.14), and residence (AOR = 0.64, 95% CI: 0.52–0.78). Overall, cervical cancer screening uptake is low in Tanzania. These findings underscore the importance of tailored interventions to improve screening rates, particularly among younger, less educated, rural-dwelling, and socioeconomically disadvantaged women. Efforts to enhance access to healthcare services, increase health literacy, and address barriers to screening participation are essential for reducing cervical cancer disparities and promoting women’s health.